Dry Transient Electronic Systems by Use of Materials that Sublime. (6th February 2017) - Kim, Bong Hoon; Kim, Jae‐Hwan; Persano, Luana; Hwang, Suk‐Won; Lee, Seungmin; Lee, Jungyup; Yu, Yongjoon; Kang, Yongseon; Won, Sang M.; Koo, Jahyun; Cho, Youn Kyoung; Hur, Gyum; et al.
Abstract : The recent emergence of materials for electronic systems that are capable of programmable self‐destruction and/or bio/eco‐resorption creates the potential for important classes of devices that cannot be easily addressed using conventional technologies, ranging from temporary biomedical implants to enviromentally benign environmental monitors to hardware secure data systems. Although most previous demonstrations rely on wet chemistry to initiate transient processes of degradation/decomposition, options in "dry transient electronic systems" could expand the range of possible uses. The work presented here introduces materials and composite systems in which sublimation under ambient conditions leads to mechanical fragmentation and disintegration of active devices upon disappearance of a supporting substrate, encapsulation layer, interlayer dielectric and/or gate dielectric. Examples span arrays of transistors based on silicon nanomembranes with specialized device designs to solar cells adapted from commercial components. Abstract : Unusual materials and device designs enable classes of electronic systems that undergo timed self‐destruction induced by ambient sublimation of a supporting substrate, encapsulation layer, interlayer dielectric and/or gate dielectric followed by resulting fragmentation of the remaining ultrathin constituent material elements.